Respuestas

  • Usuario de Brainly
2013-03-05T23:37:28+01:00

7x-1.... 5-2x...... 4x -3......  1+4x

------ - --------- = -------- + ----------

  3.......... 2x............4.............3x

 

2x(7x-1) - 3(5-2x) ........3x(4x - 3)+ 4(1+4x)

------------------------- = -------------------------------

       6x...................................12x

 

14x² - 14x - 15 + 6x ........12x² - 9x+ 4+ 16x

----------------------------- = -------------------------------

       6x...................................12x

 

14x² - 8x - 15 ...................12x² + 7x + 4

----------------------- = ---------------------------

    6x ...................................12x

 

 

(14x² - 8x - 15)12x ....... 12x² + 7x + 4

---------------------------- = ---------------------------

    6x ..

 

(14x² - 8x - 15)2 = 12x² + 7x + 4

28x² - 16x - 30 = 12x² + 7x + 4 28x² - 16x - 30 - 12x² - 7x - 4 =  16x² - 23x - 34 = 0 x1= 2,44..........x2= - 0,90   espero que te sirva, salu2!!!